1990
DOI: 10.1099/00221287-136-12-2545
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of casein and amino acids by Streptococcus sanguis P4A7 in continuous culture

Abstract: Streptococcus sang& P4A7 was grown in glucose limited conditions in continuous culture at pH 7-0 in a chemically defined medium containing either free amino acids or casein as the organic nitrogen source. Apart from aspartate and threonine, which were poorly utilized at the higher dilution rates, all amino acids in the free-amino-acid medium were utilized to various extents. At the higher dilution rates, aspartate actually increased in concentration, probably due to deamidation of asparagine. The amino acid mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…6,7 In a further series of experiments we demonstrated that, because of their peptidase activities, a number of common plaque organisms, such as S. sanguis, can obtain the metabolically important Arg from a variety of peptides and also from whole proteins, such as casein. 8,9 Studies such as these indicate that the microbial homeostasis maintained in most sites throughout the human body can be disturbed by a number of environmental factors, such as nutrient availability. One of the best-documented examples of this is the outgrowth of the cariogenic MS when diets are high in fermentable carbohydrate, especially sucrose.…”
Section: The Physiology Of Oral Streptococci and Their Interactionsmentioning
confidence: 99%
“…6,7 In a further series of experiments we demonstrated that, because of their peptidase activities, a number of common plaque organisms, such as S. sanguis, can obtain the metabolically important Arg from a variety of peptides and also from whole proteins, such as casein. 8,9 Studies such as these indicate that the microbial homeostasis maintained in most sites throughout the human body can be disturbed by a number of environmental factors, such as nutrient availability. One of the best-documented examples of this is the outgrowth of the cariogenic MS when diets are high in fermentable carbohydrate, especially sucrose.…”
Section: The Physiology Of Oral Streptococci and Their Interactionsmentioning
confidence: 99%